teacher characteristic in the 21 Factor Analysis of Teacher Characteristic in the 21st Century - คนึงเพียร อัมพร (Community and Social Development Journal, 2019)
The purposes of this research were factor analysis of teacher characteristic in the 21st century and perform a confirmatory factor analysis of teacher characteristic in the 21st century on hypothesis model with empirical data. The sample consisted of 691 subjects comprised students, teachers, parents of students and school board of Surawittayakarn School Surin of academic year 2018. The research instrument was teacher characteristic in the 21st century questionnaires; five-rating scale; 12 Latent variables; 82 Observable variables. 1. The teacher characteristic in the 21st century questionnaires were 12 Latent variables, i.e. Using innovation and technology, Good personality, Communication skills, Expertise In measurement and evaluation, Curriculum development, Classroom management, Self-development Cooperation And leadership. The construct validity was verified by one-order confirmatory factor analysis and found that the 12 model was consistent with empirical data. 2. The construct validity was verified by second-order confirmatory factor analysis and found that the 12 model was consistent with empirical data. The chi – square goodness of Fit (Chi Square) was 5849.318, the DF was 2173 , the p-value (P) was 0.00 , The Goodness-of –Fit Index (GFI) was 0.815, The Adjusted Goodness –of- Fit Index (AGFI) was 0.724 , The Normed Fit Index (NFI) was 0.902 , The Incremental Fit Index (IFI) was 0.936 , The Comparative Fit Index (CFI) was 0.935 , The Tucker – Lewis Index (TLI) was 0.905 , The Root Mean Square Error of Approximation (RMSEA) was 0.050.